Social Network Usage and the Risk of NEET Status: Exploring Gender as a Moderator - Nguyen, Pham Ngoc Thien (Journal of Social and Scientific Education, 2025)
The increasing prevalence of social network usage has raised concerns among educators and policymakers regarding its potential impact on young people's employment and education status. This study examines the relationship between active social network usage (ASNU), passive social network usage (PSNU), and the risk of being Not in Employment, Education, or Training (NEET) among undergraduates, with a focus on gender differences. A cross-sectional survey was conducted among 523 undergraduates from universities in Vietnam using both online (Google Forms) and paper-and-pencil data collection methods. Data were analyzed to explore correlations and moderation effects. The findings indicate that higher ASNU and PSNU are associated with an increased risk of NEET status. While gender did not significantly moderate this relationship among male students, a moderating effect was observed among female students. These results highlight the importance of understanding social media consumption patterns in addressing NEET risk. Policymakers and educators should consider gender-specific interventions to mitigate the potential negative impacts of social network usage on students' career and educational outcomes.